2018
DOI: 10.1080/20002297.2018.1428005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of Streptococcus mutans-induced aggravation of non-alcoholic steatohepatitis in mice

Abstract: Background: We previously reported that intravenous administration of Streptococcus mutans strain TW871 caused typical non-alcoholic steatohepatitis (NASH)-like findings in a high-fat diet (HFD) mouse model at 16 weeks after initiating the experiment. Objective: The purpose of the present study was to analyse mice administered S. mutans TW871 fed a HFD for various periods of time. Methods: First, 6-week-old C57BL/6J mice were fed an HFD for 4 weeks, then TW871 (1 × 107 CFU) or phosphate-buffered saline (PBS) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…However, it remains unknown whether this finding is consistent with previous animal studies. In animal models, intravenous administration of cnm -positive S. mutans was shown to accumulate in the liver and aggregated NASH,11 12 while we detected cnm -positive S. mutans in oral cavities, not in the blood. To explain this contradiction, it is necessary to introduce the unique host–pathogen interaction in the periodontal crevice and evaluate the bacterial properties of S. mutans .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, it remains unknown whether this finding is consistent with previous animal studies. In animal models, intravenous administration of cnm -positive S. mutans was shown to accumulate in the liver and aggregated NASH,11 12 while we detected cnm -positive S. mutans in oral cavities, not in the blood. To explain this contradiction, it is necessary to introduce the unique host–pathogen interaction in the periodontal crevice and evaluate the bacterial properties of S. mutans .…”
Section: Discussionmentioning
confidence: 57%
“…Focusing on the specific strain Streptococcus mutans , which is one of the major causative pathogens of dental caries, we suggested the role of this bacterium in development of systemic diseases including inflammatory bowel disease,7 immunoglobulin A nephropathy,8 and intracerebral haemorrhage 9 10. Moreover, we identified the contribution of cnm gene-positive S. mutans expressing the collagen-binding protein, Cnm, on the cell surface ( cnm -positive S. mutans ), to the aggravation of NASH in obesity model mice 11 12. However, in humans, the relationship between NASH and oral hygiene, with a focus on cnm -positive S. mutans infection, remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…In another study with rats, the microvesicular steatosis in the liver caused by periodontitis is reversible after removal of the ligature (Dos Santos Carvalho et al., ). Meanwhile, recent studies showed that S. mutans , a major dental caries pathogen, could induce non‐alcoholic steatohepatitis (NASH) in a mouse model (Naka et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered to be the major bacteria responsible for dental caries, which is another major cause for the tooth loss (Richards et al., ). Evidence from both human and animal studies have indicated the possible associations between S. mutans and systemic diseases such as infective endocarditis (Moreillon & Que, ), atheromatous plaque specimens (Nakano et al., ), as well as NASH (Naka et al., , ). Therefore, the association between tooth loss and NAFLD may reflect the detrimental impact of S. mutans on both oral and systemic health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation